2013
DOI: 10.1118/1.4802731
|View full text |Cite
|
Sign up to set email alerts
|

Determination of transit dose profile for a 192Ir HDR source

Abstract: The present work demonstrated that the transit dose correction based on average source speed fails to accurately correct the dose, indicating that the correct speed profile should be considered. The impact on total dose due to the transit dose correction near the dwell positions is significant and should be considered more carefully in treatments with high dose rate, several catheters, multiple dwell positions, small dwell times, and several fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The transit dose component of a brachytherapy source movement from the safe to the dwell positions, between the dwell positions, and when returning to the safe has been studied previously, [1][2][3][4][5][6][7] reporting differences up to a factor of 10 for the source speed for the same afterloader. 8 The effect of these differences on the transit dose component for clinical brachytherapy treatments performed with a HDR 192 Ir source was evaluated recently.…”
Section: Introductionmentioning
confidence: 99%
“…The transit dose component of a brachytherapy source movement from the safe to the dwell positions, between the dwell positions, and when returning to the safe has been studied previously, [1][2][3][4][5][6][7] reporting differences up to a factor of 10 for the source speed for the same afterloader. 8 The effect of these differences on the transit dose component for clinical brachytherapy treatments performed with a HDR 192 Ir source was evaluated recently.…”
Section: Introductionmentioning
confidence: 99%
“…HDR source transit dose has long been recognized and explored by many researchers using various methods [26,3842]. Among them, Fonseca, et al have extensively evaluated the transit dose of the 192 Ir HDR afterloader, with respect to the source speed profiles, for a more realistic dose correction [3840]. For the skin applicator however only one dwell position is used and the absolute transit dose contribution is a function of source activity only.…”
Section: Discussionmentioning
confidence: 99%
“…13 A single dwell position was selected in this work, as multiple dwell positions tend to increase the contribution of the 192 Ir transit dose. 43 In order to verify the accuracy of the HDR 192 Ir source for the specific dwell position, preliminary verifications with radiochromic film were performed. 44 The results demonstrated that our HDR afterloading system has a precision lower than 1 mm in the source positioning for a single dwell positioning case.…”
Section: C Hdr 192 Ir Irradiationmentioning
confidence: 99%
“…Following a similar approach used by Fonseca et al, 43 two separate simulations were done, air-kerma-strength (S k ) and the dose-to-water rate at 1 cm at 90 • . 2,3 All simulations were done according to the methodology proposed by Ballester et al 52 We obtained the value (1.111 ± 0.002) cGy.h −1 .U −1 which agrees within −0.49% with the updated consensus dose rate constant for the GammaMedplus iX source.…”
Section: B1 Monte Carlo Source Validationmentioning
confidence: 99%